2016
DOI: 10.1177/2041419616659572
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the blast wave decay coefficient using the Kingery–Bulmash data

Abstract: A growing interest for the design of structures to sustain blast-induced loads has been observed in recent years as a result of the worldwide rise of terrorist bombing attacks. The blast loading is usually characterized by a sudden increase in the pressure followed by an exponential decay. The parameters of this pressure pulse are essential for design and can be found in various blast design manuals available in the open literature. One of the most widely used sources is a technical report by Kingery-Bulmash, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 27 publications
1
59
0
2
Order By: Relevance
“…In this study, we used a localized blast load developed by Friedlander, with the positive phase using an exponential function and the negative phase using the cubic negative phase developed by Ganstrӧm [13]. Rigby et al [14] showed that for the negative phase of a Friedlander load, the cubic negative phase approach yields the most accurate results.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used a localized blast load developed by Friedlander, with the positive phase using an exponential function and the negative phase using the cubic negative phase developed by Ganstrӧm [13]. Rigby et al [14] showed that for the negative phase of a Friedlander load, the cubic negative phase approach yields the most accurate results.…”
Section: Resultsmentioning
confidence: 99%
“…) . e ( 1)Pe is effective pressure, P0 is the atmospheric pressure, Pso is the peak positive pressure, t is current time and td is time duration of positive pressure (Karlos et al, 2015).…”
Section: Load Blast Enhanced (Lbe) Methodsmentioning
confidence: 99%
“…There exist numerous manuals, relationships and graphs for calculating the generated blast load after an explosion. A comparison among the various available relationships for the main blast parameters [19] has revealed considerable differences in the proposed values. The most widely accepted approach appears to be that of Kingery and Bulmash [20], as it includes polynomial relationships for calculating the main parameters for both incident and reflected blast waves of spherical and hemispherical bursts.…”
Section: Distribution Of Uncertaintiesmentioning
confidence: 99%
“…The most widely accepted approach appears to be that of Kingery and Bulmash [20], as it includes polynomial relationships for calculating the main parameters for both incident and reflected blast waves of spherical and hemispherical bursts. By using these parameters in a deterministic manner, the large uncertainties that characterize the extreme nature of explosions are neglected, and this is not always on the conservative side [19]. If, on the other hand, a probabilistic risk assessment methodology in the design of new and existing engineering structures is followed, the quantification of the uncertainty in the calculation of the blast parameters is required.…”
Section: Distribution Of Uncertaintiesmentioning
confidence: 99%